Restoring normoglycaemia: not so harmless - Preiser, Jean-Charles (BioMed Central, 2008)
Three independent studies of tight glucose control were recently stopped prematurely due to an excess mortality in the intensive treatment arm. This commentary briefly discusses the potential mechanisms and reminds the potential benefits of physiological stress hyperglycemia.